Analisis Minat Penggunaan Aplikasi Investasi Digital pada Investor Milenial Melalui Pendekatan Theory of Planned Behavior - Nugraheni, Titin; Mahardhika, Arya Samudra (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
This research aims to empirically test the interest of millennial generation investors to use the Profits Anywhere investment application by using Theory of Planned Behavior to explain and analyze how behavior is formed through attitude toward behavior, subjective norms and perceived behavior control in making decisions. This research used a quantitative research with primary data as the data source. Using purposive sampling as the sampling technique, the number of respondents in this research were 140 respondents in total. All the datas were analyzed using SEM-PLS with WarpPLS 8.0 as the test tool. The results in this study indicate that attitude toward behavior and perceived behavior control have a positive influence on the intention. On the other hand, subjective norms do not affect Intention. Based on the value of R-Square the variables magnitude attitude toward behavior, subjective norm dan perceived behavior control to intention is 0.646 or 64,6%. The remaining 35,4% influenced by other variables outside the other outside the research. Keywords: Attitude toward Behavior; Subjective Norm; Perceived Behavior Control; Intention